Comparing Situational and Motor Abilities Among Kosovo Junior Basketball Players in Super and Unique Leagues - Begu, Bujar; Miftari, Florian; Dalip, Metin; Haxhnikaj, Labinot (Physical Education Theory and Methodology, 2023)
Study purpose. The aim of this study is to differentiate the situational and motor abilities between two leagues of junior basketball players in Kosovo. A total of 120 players, aged 18, were assessed in this research, with 60 players belonging to the Super League and the remaining 60 players from the Unique League. Materials and methods. In this research, the measuring instruments employed included a set of 12 basic motor variables and 5 situational motor variables. To ensure precise speed and agility data, electronic sensors in the form of Witty timer (Microgate) were utilized. The statistical analyses conducted involved the application of the t-test to identify significant differences between the leagues for individual variables, while the canonical discriminant analysis was employed to differentiate between the two leagues based on the comprehensive set of measured variables. Results. Differences were observed in specific variables, favoring the Super League players in areas such as abdominal muscles endurance (p < 0.05) and throwing the medicine ball (p < 0.01), while the Unique League players excelled in jump height and agility tests. T-test and discriminant analysis confirmed significant distinctions between the leagues (p < 0.01). These findings provide valuable insights into the contrasting abilities of players in the two leagues. Conclusions. This study found significant differences between the Super League and Unique League among U18 basketball players in Kosovo. The Super League players showed superior performance in explosive upper body strength, repetitive strength, and agility, while the Unique League players displayed higher physical preparedness in basic motor skills.